Collaborative learning activities supported by intelligent agents - Alves, Paulo (2007)
The changes introduced by the Bologna Process in the educational paradigm, moving from a lecturer centered paradigm to a learner centered paradigm, involves a more supported learning process based on learning outcomes and the adoption of new pedagogical methodologies. To improve the learning process and facilitate the student support, we propose the adoption of intelligent agents in learning environments, with the mission to follow closely the student in their learning activities, coaching, advertising for difficulties, adapting the context to the learner profile, and making a connection between the student and the lecturer. The adoption of artificial intelligence in education has the goal to improve the learning process adapting the contents and the learning environment to the student profile. The student profile is based on her learning style, learning needs, goals and choices.